Related Case Of Current Process Of Claiming Oleh Children Through Restorative Justice In The Way Of Law Polres Binjai - Ferry Irmawan; Firman Halawa; Muhammad Arif Sahlepi (CV. AFDIFAL MAJU BERKAH, 2024)
Traffic accidents involving juvenile perpetrators often raise controversy in the implementation of criminal law, causing much polemic. The view that the legal process should be carried out and enforced without the rule of law and law enforcement is that the